Odpowiedzi

2010-02-08T16:32:21+01:00
1.
0,3*(1-0,4x)=-0,42
0,3-0,12x=-0,42
-0,12x=-0,42-0,3
-0,12x=-0,72
x=6
spr:
0,3*(1-0,4*6)=-0,42
0,3-0,72 =-0,42
-0,42=-0,42

2.
3/4*(x-0,2)=3,5x
0,75x-0,15=3,5x
0,75x-3,5x=0,15
-2,75x=0,15
x=-6/11
spr:
3/4*(-6/11-0,2)=3,5*(-6/11)
-18/44-0,15=-21/11
-21/11=-21/11

3.
1/7*(x+1,4)=0,1
1/7x+0,2=0,1
1/7x=0,1-0,2
1/7x=-0,1
x=-0,7
spr:
1/7*(-0,7+1,4=0,1
-0,1+0,2=0,1
0,1=0,1
2010-02-08T16:41:42+01:00
0,3*(1-0,4x)=-0,42
0,3-0,12x=-0,42
-0,12x= -0,42-0,3
-0,12x= -0,72 / :(-0,12)
x = 6

sprawdzenie
0,3*(1-0,4x)=-0,42
0,3*(1-0,4*6)=-0,42
0,3*(1-2,4)=-0,42
0,3*(-1,4)=-0,42
-0,42 = -0,42
L=P

3/4*(x-0,2)=3,5x
¾x-⅜= ⁷/₂ x
¾x-⁷/₂ x =⅜
¾x-¹⁴/₄x=⅜
-¹¹/₄x =⅜ / * (-⁴/₁₁)
x=-³/₂₂

sprawdzenie
3/4*(x-0,2)=3,5x
¾*(-³/₂₂) -⅜= ⁷/₂ *(-³/₂₂)
-⁹/₈₈-⅜ = -²¹/₄₄
-⁹/₈₈-³³/₈₈ = -²¹/₄₄
-⁴²/₈₈ = -²¹/₄₄
-²¹/₄₄ = -²¹/₄₄
L=P


1/7*(x+1,4)+0,1 = 0
¹/₇*(x+ ⁷/₅) +¹/₁₀ = 0
¹/₇x +⅕+¹/₁₀ = 0
¹/₇x = -⅕-¹/₁₀
¹/₇x = -²/₁₀-¹/₁₀
¹/₇x = -³/₁₀ / *7
x = -²¹/₁₀

sprawdzenie
1/7*(x+1,4)+0,1 = 0
¹/₇*(x+ ⁷/₅) +¹/₁₀ = 0
¹/₇x +⅕+¹/₁₀ = 0
¹/₇ *(-²¹/₁₀) +⅕+¹/₁₀ = 0
-³/₁₀+²/₁₀+¹/₁₀ = 0
0=0
L=P